Structure, composition spécifique et diversité des ligneux dans deux zones contrastées en zone Sahélienne du Burkina Faso - Ouango Maurice Savadogo; Korodjouma Ouattara; Souleymane Pare; Issa Ouedraogo; Séraphine Sawadogo-Kaboré; Jennie Barron; Nabsanna Prosper Zombre (VertigO)
This study conducted in the Sahel of Burkina Faso presents the current state of woody vegetation in this region so as to establish the link between the reality on the ground and satellite observations in two sites within each of the two contrasted zones ; one presenting a certain rate of re-greening and the other of degradation. It also analyzes the specific composition, the structure, ligneous diversity and the similarities between four sites (two sites by two zones). The study used a stratified random sampling method analyzing 104 plots of 20 x 20 sqm. Statistical analysis showed significant differences in density, number of species, height class, diameter class and Simpson and Shannon indices between the two zones. The highest values were observed in the re-greening zone. We also noted a significant difference in density, diameters and heights according to land use. The fields in the re-greening zone have the highest values of density and height, but the lowest diameters. The re-greening in the Sahel is more apparent in the fields.